Head injuries in accident and emergency departments. How different are children from adults?. Issue 2 (June 1990) - Brookes, M; MacMillan, R; Cully, S; Anderson, E; Murray, S; Mendelow, A D; Jennett, B
Abstract : STUDY OBJECTIVE–The aim of the study was to examine the differences between child and adult patients attending accident and emergency departments after recent head injuries. DESIGN AND SETTING–A retrospective survey based on existing case records from 23 Scottish accident and emergency departments for 1985 was compared with prospective data from one hospital over 9 months in 1984. PATIENTS–3838 children under 15 and 4775 adults attended hospital with head injuries during the period analysed. MAIN RESULTS–Only 9% of children and 20% of adults had evidence of brain damage (altered consciousness on arrival, or history of altered consciousness with amnesia on arrival). Scalp lacerations were recorded in approximately 40% of both children and adults, more commonly in those without brain damage. Fewer children than adults had a skull x ray; in both age groups x rays were more often done if there was evidence of brain damage, headache, or vomiting, and less often when there was a scalp laceration. Only 11% of children were admitted compared with 20% of adults. Admission rates per 100, 000 population per year were 4011 for children and 1473 for adults (1967 overall); admission rates for brain damage were 290 for children and 341 for adults (331 overall). CONCLUSIONS–These are the first population based estimates of frequency of head injuries presenting at accident and emergency departments, analysed by age, gender and cause of injury. They should be of value when planning services for the head injured.